Changes and continuities in subsistence and interaction between marine hunter-gatherer and agro-pottery societies during the late Holocene in the Northern Archipelago, Patagonia, Chile - Reyes, Omar; Tessone, Augusto; Belmar, Carolina; San Roman Bontes, Manuel Julio; Morello Repetto, Flavia; Moraga, Mauricio; Urbina, Ximena (My University, 2023)
Distinctive cultural systems converged during the Late Holocene in the northern Patagonian Archipelago (similar to 41 degrees 30'-47 degrees S), connecting groups with ceramic-bearing cultural traditions and economies based on food production (horticultural) with groups of marine hunter-gatherer-fishers established since the Middle Holocene. This article evaluates changes and continuities in the subsistence and dietary patterns of the groups that occupied this archipelago throughout its occupation sequence, based on the results of delta C-13 and delta N-15 value analysis of 27 individual human remains (similar to 4400-150 cal yr BP) from the Chiloe Archipelago (similar to 41 degrees 30'-43 degrees S). These data are integrated with information previously obtained from 36 individuals (similar to 2000-300 cal yr BP) from the Chonos Archipelago (similar to 43 degrees-47 degrees S), as well as complementary samples of algae and archaeofauna. From the estimated diet of 63 individuals, we suggest a low intensity of interaction between these cultural trajectories over time in the northern Patagonian Archipelago, and continuity of hunting, fishing, and marine gathering systems. After European contact, significant changes in the subsistence of these human groups would be reflected, particularly in the Chiloe Archipelago.
Keywords: northern patagonian archipelago; middle/late holocene; diet and subsistence; stable isotopes; marine huntergatherers